2013
DOI: 10.1017/s1461145711001659
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 receptor gene variation: impact on electroconvulsive therapy response and ventral striatum responsiveness in depression

Abstract: Dysfunction of dopamine D₃ receptors, particularly in the mesocorticolimbic system, has been linked to the pathogenesis of major depression. Preclinical data show enhanced D₃ receptor binding in the striatum upon antidepressant medication and electroconvulsive therapy (ECT). Thus, the potential impact of dopamine D₃ receptor gene (DRD3) variation on ECT outcome in treatment-resistant major depression was evaluated by applying a combined molecular and imaging genetic approach. Altogether, 10 representative vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 95 publications
1
18
0
Order By: Relevance
“…Research has consistently demonstrated that depressive symptoms are often induced by impaired functioning of the dopaminergic system, particularly dopamine receptors (e.g., Dannlowski et al 2013;Kapur and Mann 1992). The dopamine D2 receptor gene (DRD2), located on chromosome 11 q2.2-2.3, is responsible for encoding of the D2 subtype of the dopamine receptor.…”
Section: Parenting the Dopamine D2 Receptor Gene And Depressive Symmentioning
confidence: 99%
“…Research has consistently demonstrated that depressive symptoms are often induced by impaired functioning of the dopaminergic system, particularly dopamine receptors (e.g., Dannlowski et al 2013;Kapur and Mann 1992). The dopamine D2 receptor gene (DRD2), located on chromosome 11 q2.2-2.3, is responsible for encoding of the D2 subtype of the dopamine receptor.…”
Section: Parenting the Dopamine D2 Receptor Gene And Depressive Symmentioning
confidence: 99%
“…Interestingly, two other polymorphisms located in the same genes (SLC6A3 rs4975646 and DRD3 rs3773679) were significantly associated (after Bonferroni correction) with WM microstructure in our OCD sample, and a further three polymorphisms (SLC6A3 rs1048953, DRD3 rs2087017 and DRD3 rs167771) also showed non-significant trends (p r0.0028; data not shown). Although these polymorphisms have not previously been related to OCD, some of them have been associated with the pathophysiology or pharmacological treatment of other psychiatric disorders (Dannlowski et al, 2013, De Krom et al, 2009Gassó et al, 2009). Clinical evidence and molecular imaging studies support the involvement of dopamine in OCD.…”
Section: Discussionmentioning
confidence: 96%
“…It is plausible that the scarcity of association findings for DRD3 and for the other dopamine receptor genes is partly due to complexity of the underlying mechanisms and inability to capture the signal when investigating one phenotype at a time. To date, single studies have identified specific DRD3 variants associating with FTND defined ND [46], heaviness of smoking index, and time to first cigarette in the morning [11], as well as treatment response and remission in depression patients [47].…”
Section: Discussionmentioning
confidence: 99%